Frequency and Associated Risk Factors of Bowel and Bladder Problem Among Children with Spastic Cerebral Palsy - Ali, Arshad; Afnan, Zavata; Anum, Amnah; Bibi, Iqra; Sibghatullah; Aslam, Fatima (Indus Journal of Bioscience Research, 2025)
Background: Cerebral paralysis (CP) is a neuro-developmental condition starting in childhood and continuing throughout life. Bowel and bladder problems are a very common problem in children with cerebral palsy, and it affects 1 in every 5 children with cerebral palsy. Objective: To find out the frequency and associated risk factors of bowel and bladder problem in spastic cerebral palsy. Methodology: A cross-sectional survey in Peshawar was conducted including 139 participant, age 5-12 years and spasticity level I-IV with spastic cerebral palsy Data was collected using convenience sampling technique. Children with any neurological disease affecting bowel and bladder issues and children with renal and genitourinary surgery were excluded. Tools used for data collection were, Gross Motor Functional Classification System for functional limitations, and Childhood bowel and bladder dysfunction questionnaire (CBBDQ) for bowel and bladder problems in children. Data was analyzed using SPSS version 22. Results: The mean age of the 139 participants was 8.33±2.29 years, with 83 males and 56 females. Bowel and bladder issues affected 68.34% of the patients. Bowel and bladder problems were significantly correlated with age group, CP type, CMFCS level, speech issue, and spasticity level (p<0.05). However, there was no significant association between bowel and bladder problems and gender, caregiver education status, Socio-economic status, positive UTI history, toilet training, use of medications and BMI (p>0.05). Conclusion: The study concluded that there is high frequency of bowel and bladder problems in children with spastic cerebral palsy. The significant risk factors associated with bowel and bladder problems were type of CP, level of spasticity, GMFCS level, speech problem and age group.